The Correlation between ABO Blood Groups and the IFN-Γ Levels in COVID 19 Infected Patients (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This investigation was conducted in the Iraqi province of Wasit in collaboration with the microbiology units of Fairouz Hospital and Alzahraa Hospital. This study's objectives were to assess interferon (IFN)-γ serum levels and this cytokine's protective role based on the ABO blood types among SARS-CoV-2 infected individuals. Samples were gathered in the province of Wasit from various locations. It had 22 healthy individuals as a control group and 66 blood samples from Iraqi patients suffering with COVID-19. The study was carried out between January and April of 2024, with both groups' ages ranging from 14 to 72. There were three patient classifications: mild (22 patients), moderate (22 patients), and severe (22 patients). All participants' serum samples were taken, and ELISA (enzyme-linked immunosorbent assay) was used to measure the levels of cytokines using monoclonal antibodies (Anti-A, B, and D). All of these tools are easily accessible in a blood test tool set. ( AntiSera ABD Blood Grouping Reagent BIOLAB-India). The ANOVA test shows that mean level was statistically not significant difference( p-value 0.649) for concentration of interferon gamma according to the blood groups.